Adjustment and Agriculture in Africa: Farmers, the State, and the World Bank in Guinea - Jennifer Clapp (Macmillan Press, 1997)
With the adoption of a World Bank-sponsored structural adjustment programme in the mid-1980s, Guinea underwent a dramatic change in its economic and agricultural policies. The country's experience over the past decade illustrates some of the most pressing problems encountered by African countries pursuing economic reform. This book analyses these difficulties by examining the adjustment experience in Guinea as it affected the country's overall political economy and the agricultural sector in particular. It also places this case within the broader context of African adjustment.